Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility